The EGFR‐P38 MAPK axis up‐regulates PD‐L1 through miR‐675‐5p and down‐regulates HLA‐ABC via hexokinase‐2 in hepatocellular carcinoma cells. Issue 1 (1st January 2021) - Liu, Zongcai; Ning, Fen; Cai, Yanna; Sheng, Huiying; Zheng, Ruidan; Yin, Xi; Lu, Zhikun; Su, Ling; Chen, Xiaodan; Zeng, Chunhua; Wang, Haifang; Liu, Li
Abstract: Background: Immunotherapy has been shown to be a promising strategy against human cancers. A better understanding of the immune regulation in hepatocellular carcinoma (HCC) could help the development of immunotherapy against HCC. The epidermal growth factor receptor (EGFR) signaling is frequently activated in HCC and plays important roles in tumorigenesis. However, its role in HCC immunity is still largely unknown. This study aimed to investigate the impact of EGFR signaling on programmed death‐ligand 1 (PD‐L1) and human leukocyte antigen class‐I (HLA‐I) expression in HCC cells and its underlying mechanisms. Methods: The expression of phosphorylated EGFR (p‐EGFR), PD‐L1, and HLA‐I (HLA‐ABC) in HCC specimens was detected by immunohistochemistry, and their correlations were analyzed. PD‐L1 and HLA‐ABC expression in EGFR‐activated HCC cells were detected by quantitative real‐time PCR, Western blotting, and flow cytometry, and T cell‐mediated lysis was performed to test the immunosuppressive effects of PD‐L1 and HLA‐ABC alterations in HCC cells. Furthermore, the underlying mechanisms of EGFR activation‐induced PD‐L1 up‐regulation and HLA‐ABC down‐regulation were explored by animal experiments, luciferase reporter assay, and gene gain‐ and loss‐of‐function studies. Results: p‐EGFR was positively correlated with PD‐L1 and negatively correlated with HLA‐ABC expression in HCCs. EGFR activation by its ligand EGF up‐regulated PD‐L1 and down‐regulated HLA‐ABC in HCC cells, which was functionally important and could be abolished by the EGFR inhibitor, gefitinib, both in vitro and in vivo . Mechanistically, enhanced P38 mitogen‐activated protein kinase (MAPK) activation down‐regulated microRNA‐675‐5p (miR‐675‐5p) and up‐regulated glycolysis‐related enzyme hexokinase 2 (HK2); miR‐675‐5p down‐regulation enhanced the stability of PD‐L1 mRNA probably via the 3'‐untranslated region (3'‐UTR) of PD‐L1 and thereby caused PD‐L1 accumulation, and HK2 up‐regulation enhanced aerobic glycolysis and mediated a decrease in HLA‐ABC. Conclusions: The EGFR‐P38 MAPK axis could up‐regulate PD‐L1 through miR‐675‐5p and down‐regulate HLA‐ABC via HK2 in HCC cells. Our study reveals a novel signaling network that may cause immune suppression in HCC and suggests that EGFR signaling can be targeted for HCC immunotherapy.